Efektifitas Pemanfaatan Dana Bantuan Operasional Pendidikan (BOP) dalam Upaya Peningkatan Mutu Pendidikan Jenjang PAUD di Kecamatan Bula Kabupaten Seram Bagian Timur - Faud, Nurjanah; Kempa, R.; Rumfot, Sumarni (LP. Ma'arif Janggan Magetan, 2024)
Permendikbud Number 2 of 2022 states that the Early Childhood Education (PAUD) Operational Assistance (BOP) is an aid fund provided by the Central Pamerintah to assist in providing funding for non-personnel operational costs in supporting early childhood education learning activities. In accordance with article 12 paragraph (1) letter (e) of the Regulation of the Minister of Finance of the Republic of Indonesia Number 116/PMK.07/2022 concerning the Management of Non-Physical Special Allocation Funds, the calculation of the allocation of Education BOP funds is carried out based on the number of students multiplied by the unit cost per student. This type of research is descriptive qualitative research with a problem formulation that combines research to explore or photograph the situation to be thoroughly researched, broadly and in depth in the early childhood education unit in Bula sub-district, namely at Bula State Guidance Kindergarten and Gumumae Bula Kindergarten. The purpose of this study itself is to determine the Effectiveness of the Management of Education Operational Assistance Funds (BOP) in an Effort to Improve the Quality of PAUD Education in Bula District, East Seram Regency and to determine the supporting and inhibiting factors in the management of educational operational assistance at Bula State Guidance Kindergarten and Gumumae Bula Kindergarten. From the results of the research conducted, it was found that BOP fund planning was carried out through the preparation of school activity plans and budgets (RKAS) by involving: school principals and staff and teacher councils, school school committees and management at the education office in charge of ECCE, the realization of the BOP Fund Program at both ECCE institutions has been completed according to the target time. Performance objectives and targets in accordance with the RKAS, the implementation/use of BOP funds at TK Pembina Bula and TK Gumumae Bula have not applied the principles of transparency and accountability in the Financial statement accountability report.At TK Pembina Bula and TK Gumumae Bula in 2022.